Effects of Biochar on the Growth and Development of Tomato Seedlings and on the Response of Tomato Plants to the Infection of Systemic Viral Agents - Luigi, Marta; Manglli, Ariana; Dragone, Immacolata; Antonelli, Maria Grazia; Contarini, Mario; Speranza, Stefano; Bertin, Sabrina; Tiberini, Antonio; Gentili, Andrea; Varvaro, Leonardo; Tomassoli, Laura; Faggioli, Francesco (Frontiers in Microbiology, 2022)
Biochar is a rich carbon product obtained by pyrolysis of biomass under a limited supply of oxygen. It is composed mainly of aromatic molecules, but its agronomic value is hard to evaluate and difficult to predict due to its great variable characteristics depending on the type of starting biomass and the conditions of pyrolysis. Anyway, it could be used as soil amendment because it increases the soil fertility of acidic soils, increases the agricultural productivity, and seems to provide protection against some foliar and soilborne diseases. In this study, the effects of biochar, obtained from olive pruning, have been evaluated on tomato seedlings growth and on their response to systemic agents' infection alone or added with beneficial microorganisms (Bacillus spp. and Trichoderma spp.). First, experimental data showed that biochar seems to promote the development of the tomato seedlings, especially at concentrations ranging from 1 to 20% (w/w with peat) without showing any antimicrobial effects on the beneficial soil bacteria at the tomato rhizosphere level and even improving their growth. Thus, those concentrations were used in growing tomato plants experimentally infected with tomato spotted wilt virus (TSWV) and potato spindle tuber viroid (PSTVd). The biochar effect was estimated by evaluating three parameters, namely, symptom expression, number of infected plants, and pathogen quantification, using RT-qPCR technique and −ΔΔCt analysis. Biochar at 10–15% and when added with Trichoderma spp. showed that it reduces the replication of PSTVd and the expression of symptoms even if it was not able to block the start of infection. The results obtained on TSWV-infected plants suggested that biochar could contribute to reducing both infection rate and virus replication. For systemic viral agents, such as PSTVd and TSWV, there are no curative control methods, and therefore, the use of prevention means, as can be assumed the use biochar, for example, in the nursery specialized in horticultural crops, can be of great help. These results can be an encouraging starting point to introduce complex biochar formulates among the sustainable managing strategies of plant systemic diseases.